PRELIMINARY STUDIES ON THE USE OF WATER ACTIVITY (AW) MEASUREMENTS FOR POSSIBLE APPLICATIONS IN THE PLANT EXTRACT INDUSTRY - van Ginkel, A.; Peña, L. R.; Villar, G. R. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The objectives of this work were firstly, the screening for aw in liquid and dry herbal extracts (20 and 24 samples respectively), from 5 different manufacturers and secondly, relating aw variations to moisture content changes of dry extracts exposed to different ambientes (three controlled humidity chambers at 98, 76 and 50% RH, at 20ºC). Aw was measured with a Dew Point Hygrometer. First results showed that aw values ranged from 0,190 to 0,420 and from 0,780 to 0,999 in dried and fluid extracts respectively and secondly as soon as the dried extracts were exposed to higher RH, a sudden increment of aw was observed while the rise of moisture content was smoother and delayed with respect to aw. The lower the initial aw value of the sample, the steeper was the increment. After 3-4 hours of exposure to 98% RH, aw reached, in some cases, values beyond 0,60 (moulds and yeasts can start developing). Also, glass transition was observed at 76% and 98% RH. This study shows that the exposure of dried herbal extracts to ambient conditions may lead to increment of aw that can affect the quality and shelf-life of the product. It also seems that aw is a more suitable tool than the moisture content for HACCP. Further research is needed to evaluate the possible moisture absorption from the ambiente that can occur when, packaging is not well sealed or/and they are exposed to moist environments, moist manufacturing and mixtures with products of higher aw, among others.